Distributed Cognition in Top Management Teams and Organizational Ambidexterity: The Influence of Transactive Memory Systems. (March 2017) - Heavey, Ciaran; Simsek, Zeki
How can a firm develop, distribute, and use knowledge more effectively and efficiently in ways that increase its ability to pursue an ambidextrous orientation? Synthesizing insights from social cognition and upper-echelons perspectives, we offer a new theoretical vantage point that brings the role of top management teams' cognitive structure to the fore and, in particular, the enabling influence of transactive memory systems. We argue that transactive memory provides a top management team with a system for generating, distributing, and integrating knowledge based on members' specific areas of expertise in ways that increase its ability to both differentiate and integrate strategic agendas for ambidexterity. From a multisource study of top management teams in a sample of technology-based small-to-medium-sized firms, we find that while top management teams with well-developed transactive memory systems are able to pursue an ambidextrous orientation, the impact of transactive memory is also shaped by diverse organizational experience and functional expertise within these teams. We discuss the scope and significance of these findings for theory, future research, and managerial practice.